IMPROVING THE PERFORMANCE OF BOILER PLANTS DUE TO THE USE OF DIRECT AND REVERSE RANKIN CYCLES (MODERN CONSTRUCTION AND ARCHITECTURE, 2023)
To generate electricity from biofuels at heat and power enterprises of Ukraine, the direct Rankine cycle is used, which ensures the efficiency of energy transformation within h = 0.25-0.55. To improve the efficiency of fuel energy, use in boiler plants, it is also proposed to implement a reverse Rankine cycle scheme. Such a proposal is good to use in enterprises where there is a need for drying biomaterials. Instead of a separate boiler for drying processes, it is proposed to use the energy of water condensation from flue gases. In this case, the cost of electricity for the operation of the compressor is significantly less than the amount of heat obtained by condensing water from flue gases. The efficiency coefficient or COP of the reverse Rankine cycle can have values greater than one h = COP > 3. The combination of direct and reverse Rankine cycles in the technological scheme of the boiler plant increases the efficiency of using primary energy sources.The paper analyzes the representation of energy as a combination of two components: the potential P and the dynamics D. The Leibniz model, in which the power N is represented as the product of the potential P and the dynamics D with the unification of the unit of measure Watt, allows calculating the efficiency of transformation processes of different types of energy. To improve the energy performance of boiler plants, further development of the Newton model is proposed, which makes it possible to calculate the process dynamism indicator – m. In Newton's model, within the framework of one type of energy, the dynamism indicator is calculated – as the ratio of dynamics to the initial potential m = D / P. Dynamism  can be calculated as the reciprocal of the resistance R, provided that the units of measurement of the energy components – potential and dynamics are unified. To increase the efficiency of biofuel combustion energy use, the idea of the reverse Rankine cycle has been implemented. The moisture condensation temperature of the flue gases increases due to an increase in the pressure of the medium. To do this, the smoke exhauster is moved from the discharge zone to the pressure zone. The additional energy from the flue gases of the boilers can be used to increase the efficiency of drying biomaterials. It is possible to refuse an additional boiler for drying materials, which significantly reduces fuel costs, and also improves the environmental performance of technological processes.
Keywords: energy; Rankine cycle; efficiency; biomass; drying.